2019
DOI: 10.3390/w11102095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation Water Salinity on Maize (Zea may L.) Emergence, Growth, Yield, Quality, and Soil Salt

Abstract: Freshwater shortage is becoming one of the major limiting factors for the sustainable development of agriculture in arid and semi-arid areas of north China. A two-year field experiment about mulched drip irrigation on maize was conducted in Hetao Irrigation District with five irrigation water salinity levels (total dissolved solids; 1, 2, 3, 4, and 5 g·L−1). The effects of irrigation water salinity on maize emergence, growth, yield, grain quality, and soil salt were determined. The results indicated that with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Cucci et al [75] found no difference in the kernel composition due to irrigation water quality in the first year of a study conducted in Italy. Contrarily, in the third year, brackish water irrigation increased the grain protein content by 6.9% and decreased the moisture content by 9.3% compared to grain irrigated with freshwater, which is similar to the findings from Li et al (2019) [73]. Finally, there was no effect of irrigation scheduling and the interaction among salinity and irrigation scheduling on grain quality either in the first or the third year under s t udy.…”
Section: Effect On Grain Qualitysupporting
confidence: 87%
See 1 more Smart Citation
“…Cucci et al [75] found no difference in the kernel composition due to irrigation water quality in the first year of a study conducted in Italy. Contrarily, in the third year, brackish water irrigation increased the grain protein content by 6.9% and decreased the moisture content by 9.3% compared to grain irrigated with freshwater, which is similar to the findings from Li et al (2019) [73]. Finally, there was no effect of irrigation scheduling and the interaction among salinity and irrigation scheduling on grain quality either in the first or the third year under s t udy.…”
Section: Effect On Grain Qualitysupporting
confidence: 87%
“…Among these, the negative impact of salt stress in grain quality has not been extensively studied. Working with five saline irrigation levels [1, 2, 3, 4, and 5 g L −1 of total dissolved solids (TDS)] in a 2-yr study in China, Li et al [73] found no difference in the oil, crude fiber and ash contents of maize grain. Conversely, grain moisture and starch content decreased with increased salinity, with maximum values ocurring with 1, 2 and 3 g L −1 of TDS in both cases, while protein content increased with increased salinity, reaching maximum values >12% with 4 and 5 g L −1 of TDS.…”
Section: Effect On Grain Qualitymentioning
confidence: 99%
“…In cereals, carbohydrates are the central reserve of grains (50-70%) followed by proteins (5-12%) [78], which determine grain textural, nutritional and taste attributes. Studies showed that high salt concentrations could reduce amylose and starch contents and modulate grain texture [66,67,74,80]. These functional changes might be due to the starch-tostorage protein ratio of grains, distribution of the amylopectin chain, amylose content, the crystallinity of starch granules and particle size [78].…”
Section: Effect Of Salinity On Grain Yield and Qualitymentioning
confidence: 99%
“…These functional changes might be due to the starch-tostorage protein ratio of grains, distribution of the amylopectin chain, amylose content, the crystallinity of starch granules and particle size [78]. In maize, for example, grain protein content increased while carbohydrate decreased with increasing salt contents in irrigation water [80]. Salinity (0.62-1.16 mS cm −1 ) decreased grain yield by 36% in rice but did not influence grain texture compared to the control treatment [73].…”
Section: Effect Of Salinity On Grain Yield and Qualitymentioning
confidence: 99%
“…The mother river of the Chinese national capital Beijing and Tianjin municipality-the Chaobai River (CBR), has given birth to generations of civilization and now is the important grain and vegetable base of the two megacities [1,2]. Nevertheless, the CBR basin was once known as a saline-alkaline, waterlogged, flood-prone and low-yielding region due to high groundwater table in the 1950s, and at that time, soil salinity constituted a major factor limiting crop production [3,4] because it affects plant growth and survival [5]. The period from 1950s onward for a few decades witnessed successful The plowing layer mainly consists of silty clay, clay silt and silt, and was formed in the Holocene.…”
Section: Introductionmentioning
confidence: 99%